Age and Parity as Risk Factors for Childbirth Complications: A Systematic Review - Erdira Natasya Putri; Cut Warnaini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Maternal deaths result from complications during, after pregnancy and childbirth. Factors affecting maternal mortality in Indonesia are 4 too and 3 too late. The main causes that account for nearly 75% of all maternal deaths are postpartum hemorrhage, infection, high blood pressure during pregnancy, complications from childbirth and unsafe abortion. This study aimed to analyze, synthesize, summarize and compare the results of one study with another on